Injury Incidence Across the Menstrual Cycle in International Footballers - Martin, Dan; Timmins, Kate; Cowie, Charlotte; Alty, Jon; Mehta, Ritan; Tang, Alicia; Varley, Ian (Frontiers in Sports and Active Living, 2021)
Objectives: This study aimed to assess the distribution of injuries in relation to menstrual cycle phase and when menstrual cycle length was extended in international footballers. Materials and Methods: Over a 4-year period, injuries from England international footballers at training camps or matches were recorded, alongside self-reported information on menstrual cycle characteristics at the point of injury. Injuries in eumenorrheic players were categorised into early follicular, late follicular or luteal phase. Frequencies were also compared between injuries recorded during the typical cycle and those that occurred after the cycle would be expected to have finished. Rates of injury per 1000 person-days were calculated, along with the expected proportions of injuries weighted to the varying phase duration between cases. Results: 156 injuries from 113 players were eligible for analysis. Rates of injury per 1000 person-days were 31.9 in the follicular, 46.8 in the late follicular and 35.4 in the luteal phase. Proportional rate ratios (observed:expected) of interest in the late follicular phase were 1:1.33 for all injuries and 1:1.71 for muscle and tendon injuries. Muscle and tendon injuries showed proportional rate ratios of 1:1.95 (muscle rupture/tear/strain/cramp) and 1:2.00 (tendon injuries/ruptures) in the late follicular phase. 20% of injuries were reported as occurring when athletes were overdue menses. Conclusion: Muscle and tendon injuries occurred approximately twice as often in the late follicular phase compared to the early follicular or luteal phase. Injury risk may be elevated in typically eumenorrheic women in the days after their next menstruation was expected to start.